(untitled) (Bulletin KNOB, 2000)
The typically Dutch country estate Oud-Amelisweerd is situated on the river Kromme Rijn between Utrecht and Bunnik. This mansion was built in 1770 and has remained unchanged ever since. The house has an interior finishing with Chinese export wallpaper and painted linen wall linings. In 1993 the SRAL examined the condition of the wall coverings and also studied the historical finishing of the paintwork on the wainscotting. In 1997 the linen wall-linings in two rooms were treated in the studio of the SRAL, one room with Chinese wall paper was conserved in situ. When treating the painted linen wall coverings, the paintwork on the wainscotting was also tackled. The Fazanten room was restored to its original state with a historical linseed-oil paint. The ’Oudhollandse’ room was reconstructed in the finishing phase that matches the wall paper and the painted ceiling. The article describes the historical sources for decoration painters and the material-technical aspects of linseed-oil paint. It also gives a detailed description of the restoration of the wall-linings and particularly the retouching and painting of large voids. The object of the restoration was a gradual and cautious method of restoration, from the starting point of regarding the interiors as ensembles. This implies that there is a relation between the components of the interior, which should not be disturbed by, for instance, cleaning just one component. In connection with this starting point, a comparison is made with the fairy tale of Sleeping Beauty; just as the princess, the house will have to be revived. However, great caution is required here.